2008
DOI: 10.1007/s10535-008-0035-2
|View full text |Cite
|
Sign up to set email alerts
|

Water stress induced changes in the leaf lipid composition of four grapevine genotypes with different drought tolerance

Abstract: To dissect differences in both lipid accumulation and composition and the role of these modifications during drought stress, four grapevine cultivars exhibiting differential tolerance to drought were subjected to water shortage. Tolerant cultivars, Kahli Kerkennah and Cardinal, exhibited higher leaf water potential (Ψ w ), and lower lipid peroxidation compared to the sensitive cultivars Guelb Sardouk and Superior Seedless during stress. Total lipid amounts increased during stress only in the leaves of the tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 19 publications
6
62
0
Order By: Relevance
“…Augusta when compared to cv. Aldana [27]. Unlike the carotenoid analysis, FT-Raman spectroscopy did not provide unambiguous results in the analysis of chlorophylls.…”
Section: Evaluation Of Pigment Contentmentioning
confidence: 88%
See 1 more Smart Citation
“…Augusta when compared to cv. Aldana [27]. Unlike the carotenoid analysis, FT-Raman spectroscopy did not provide unambiguous results in the analysis of chlorophylls.…”
Section: Evaluation Of Pigment Contentmentioning
confidence: 88%
“…However, these changes very often depend on the genotype and on the type of stress. Toumi et al (2008) [27] studied grapevine under drought stress, and observed changes in the composition of total lipids towards the increase of the proportion of 18:3. The increase in the percentage of 18:3 under the influence of drought was also reported in the study of Gigon et al (2004) [28] in certain lipid fractions (DGDG and phosphatidylcholine fraction) in Arabidopsis thaliana L. What is more, these authors found an overall decrease in the amount of lipids reaching even 75% as a result of drought.…”
Section: Fatty Acid Assaymentioning
confidence: 99%
“…Being the most widely cultivated perennial plant, grapevine occupies a privileged position and has the greatest economic value worldwide, as well as in Tunisia. However, autochthonous Tunisian grapevine varieties exhibit enhanced osmotic tolerance and adaptive responses to stress conditions [1][2] which represent a valuable resource for studying mechanisms of adaptation to salinity and drought in V. vinifera. Thus understanding the molecular genetic basis of the environmental stress responses would be crucial towards improving grapevines production.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of work on the mechanism of drought damage to Pallavi and Rama, 2005;Jan, 2006;Toumi et. al., 2008).…”
mentioning
confidence: 99%